Evaluasi Pertumbuhan dan Keragaman Genetik Tanaman Palahlar Gunung (Dipterocarpus retusus blume.) dan Palahlar (Dipterocarpus hasseltii blume.) Berdasarkan Penanda RAPD - Detty Sumiyati; Fifi Gus Dwiyati; I Istomo; Iskandar Zulkarnaen Siregar (Institut Pertanian Bogor (IPB University), 2009)
Dipterocarpus hasseltii (palahlar) and Dipterocarpus retusus (mountain palahlar) are plant species of Dipterocarpaceae family that originate from West Java which population is getting rare. Information about growth development and genetic variation of palahlar is important to support culturing program and its genetic conservation. One of the techniques to study palahlar growth is through observation of the plant height and stem diameter increment. DNA analysis is use to gain information of palahlar genetic diversity. One of the DNA based molecular marker widely used as plant genetic marker is RAPD. There were 2 primary that resulting the best amplifying quality in genetic diversity analysis that was OPO-13 dan OPY 20. Analysis result with POPGENE 32 was resulting average genetic diversity between classes as much as 0.1869. The biggest genetic diversity for palahlar was on the medium growth class as much as 0.2498 dan for mountain palahlar was in small growth class as much as 0.2240. Cluster analysis shows that there were 2 big groups that were medium-high growth class group and small growth class group. Dendrogram shows that there were 2 species in one group, that was palahlar and mountain palahlar that was in one group of small growth class. The closed genetic distance existed between medium growth class group of palahlar and high growth class group (0.0383), while the far distance is between palahlar of small growth class group with mountain palahlar of mediaum growth class group as much as 0.1826.